Social relationships, inflammation markers, and breast cancer incidence in the Women's Health Initiative. (June 2018) - Busch, Evan L.; Whitsel, Eric A.; Kroenke, Candyce H.; Yang, Yang C.
Abstract: Objectives: Previous research has reported associations between social relationships and carcinogenesis. Inflammation is a potential mediator of these associations. To clarify these links for one tumor site, we examined associations between social relationships, circulating inflammation markers, and breast cancer incidence. Materials and Methods: Among 132, 262 participants from the prospective Women's Health Initiative, we used linear and logistic regression to evaluate associations between social relationship characteristics (social support, social strain, social network size) and inflammation markers of C -reactive protein (CRP) and white blood cell count (WBC). Cox regression was used to evaluate associations between inflammation markers and breast cancer incidence, as well as associations between social relationship characteristics and breast cancer incidence with and without adjustment for inflammation markers. Results: Larger social networks were associated with lower continuous CRP (beta = −0.22, 95% CI -0.36, −0.08) and WBC (beta = −0.23, 95% CI -0.31, −0.16). Greater social strain was associated with higher continuous CRP (beta = 0.24, 95% CI 0.14, 0.33) and WBC (beta = 0.09, 95% CI 0.04, 0.14). When WBC was dichotomized at 10, 000 cells/uL, high WBC was associated with greater hazards of in situ breast cancer (HR = 1.65, 95% CI 1.17, 2.33) but not invasive breast cancer. Social relationship characteristics were not associated with incidence of invasive or in situ breast cancer. Conclusion: Larger social networks were associated with lower inflammation and greater social strain was associated with higher inflammation. Higher inflammation might be associated with development of in situ breast cancer, but this appeared to be due to factors other than social relationships. Highlights: Social relationships and breast cancer have been associated. The potential role of inflammation as a mediator of these associations was evaluated. Larger social networks were associated with lower inflammation. Greater social strain was associated with higher inflammation. Greater inflammation was associated with greater hazards of in situ breast cancer.